1997
DOI: 10.1101/gr.7.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of quantitative trait loci for ethanol sensitivity in long-sleep and short-sleep mice.

Abstract: Initial insensitivity to alcohol is a strong predictor of human alcoholism, a widespread and heritable health problem. The Long Sleep and Short Sleep lines of mice were developed by genetic selection for high or low alcohol sensitivity. We have identified seven quantitative trait loci (QTLs) specifying differences in alcohol sensitivity using intercross progeny from these selected strains. These QTLs (LoreI-LoreT) together account for -60% of the total genetic variance for this trait. This represents the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 34 publications
(36 reference statements)
10
101
1
Order By: Relevance
“…A study of the mice with the most extreme scores in a sample of 1072 [F.sub.2] hybrids supported only two of these QTLs, which were tentatively localized within intervals of about 16 cM (Markel et al 1997). As a further test, [F.sub.2] hybrid mice of known genotype at the marker loci flanking the hypothetical QTL were then mated and their offspring tested for ethanol-induced sleeping (Bennett et al 1997). Although the sample sizes were too small to yield conclusive results, this application of marker-assisted selection (Ruane & Colleau 1995) holds great promise for confirming the presence of a QTL, localizing it to a narrower interval, and studying interlocus interactions.…”
Section: Quantitative Trait Locimentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the mice with the most extreme scores in a sample of 1072 [F.sub.2] hybrids supported only two of these QTLs, which were tentatively localized within intervals of about 16 cM (Markel et al 1997). As a further test, [F.sub.2] hybrid mice of known genotype at the marker loci flanking the hypothetical QTL were then mated and their offspring tested for ethanol-induced sleeping (Bennett et al 1997). Although the sample sizes were too small to yield conclusive results, this application of marker-assisted selection (Ruane & Colleau 1995) holds great promise for confirming the presence of a QTL, localizing it to a narrower interval, and studying interlocus interactions.…”
Section: Quantitative Trait Locimentioning
confidence: 99%
“…When 124 markers were tested in 27 RI strains derived from the long sleep (LS) and short sleep (SS) lines, 11 "provisional QTLs" were located with a very lenient ([Alpha] = 0.05) criterion (Markel et al 1996). A study of the mice with the most extreme scores in a sample of 1072 [F.sub.2] hybrids supported only two of these QTLs, which were tentatively localized within intervals of about 16 cM (Markel et al 1997). As a further test, [F.sub.2] hybrid mice of known genotype at the marker loci flanking the hypothetical QTL were then mated and their offspring tested for ethanol-induced sleeping (Bennett et al 1997).…”
Section: Quantitative Trait Locimentioning
confidence: 99%
“…One school of thought holds that stringent significance levels should be imposed; 1,2 another suggests more modest criteria for QTL nomination, with subsequent confirmation trials with independent samples. 3-5 Recombinant inbred strains 6,7 and various types of intercrosses 8,9 have been used in correlational designs, both for nomination and confirmation studies. Alternative experimental procedures include knockout preparations 10 and short-term phenotypic selective breeding.…”
Section: Quantitative Genetic Research Has Produced a Wealth Ofmentioning
confidence: 99%
“…(PCP) by Alexander et al 21 and for hypnotic dose sensitivity to alcohol by Markel et al 9 For chromosome 15, the markers D15Mit60 and D15Mit63, located at 26.1 and 37.6 cM, 17 were assessed Interval analysis of F 2 data for chromosome 12 revealed no statistically significant lod score, and there in the GS 0 . Seven matings of homozygote parents produced 15 female and 13 male offspring homozygous for were no significant differences between the GS 1 groups for increasing and decreasing chromosome 12 haplothe haplotypes defined by the increasing alleles for both markers, and five matings produced 16 female and types (P values for males and for females were 0.11 and 0.14, respectively).…”
Section: Quantitative Genetic Research Has Produced a Wealth Ofmentioning
confidence: 99%
“…Zfp142 and Zfp133 are implicated in quantitative trait locus (QTL) studies of initial sensitivity to alcohol. QTL intervals were mapped in inbred lines 31,32 and coding differences between lines were identified in eight genes in the QTL intervals. Mapping in interval-specific congenic recombinant mice, 33 which carry smaller, overlapping sections of the QTL intervals, showed that only the observed coding sequence changes in Zfp142 or Ptprn in one interval, and Zfp133 in another, could account for the phenotypic difference.…”
Section: Discussionmentioning
confidence: 99%